Life expectancy in hereditary cancer predisposing diseases: an observational study. Issue 4 (23rd February 2012) - Wilding, Anna; Ingham, Sarah Louise; Lalloo, Fiona; Clancy, Tara; Huson, Susan M; Moran, Anthony; Evans, D Gareth
Abstract : Background: Neurofibromatosis 1 (NF1), neurofibromatosis 2 (NF2), familial adenomatous polyposis (FAP), von Hippel-Lindau syndrome (VHL), and Gorlin syndrome (GS) are single gene diseases that predispose to early onset tumours. Few studies have assessed the effect of these diseases on life expectancy. This study's aim was to assess this effect, and to test the hypothesis that genetic registers increase survival. Method: NF1, NF2, VHL, FAP, and GS patients were identified through the North West Regional Genetic Register Service and the North West Cancer Intelligence Service. Information on benign and malignant tumours, and deaths were obtained. Kaplan–Meier curves were used to show actuarial survival rates for each disease, compared to the local population, and in patients diagnosed pre/post the regional genetic register. Log rank (Mantel–Cox) tests were used to compare survival between groups. Results: Life expectancies were significantly reduced for all diseases investigated compared with the local population (80.0 years) (p=0.05). GS had the longest life expectancy at 73.4 years, followed by NF1 at 71.5 years, NF2 at 69.0 years, FAP at 63.6 years, and VHL at 52.5 years. Patients diagnosed after establishment of the genetic register had an increase in survival compared to those diagnosed pre-1990: NF2 (14.7 years), FAP (13.9 years), VHL (16.3 years), and GS (11.2 years). Conclusion: Life expectancy for all five diseases was less than normal, although in recent years this reached the level of the local population in GS. Although there have been improvements in all conditions which may in part be attributable to better targeted care through the genetic register service, more needs to be done to address the very poor life expectancy in VHL.